EXTRADITION BY THE INDONESIAN NATIONAL POLICE OF PERPETRATORS OF CORRUPTION FROM INDONESIA, BASED ON THE LEGAL PROVISIONS OF THE INTERNATIONAL CRIMINAL POLICE ORGANIZATION (ICPO-INTERPOL) - Bajang Barokhatul Kholisoh; Suswoto (Fakultas Hukum Universitas Janabadra, 2022)
Interpol is an organization formed to coordinate cooperation between police in countries around the world. Advances in technology, information, and communication have increased the intensity of transnational crime. The extradition treaty has an important role in preventing and overcoming perpetrators of international crimes, especially perpetrators of corruption who fled from Indonesia to other countries, whether they are still suspects, defendants, or convicts. The formulation of the problem in this study is how the role of the Police in the practice of carrying out the extradition of perpetrators of corruption, legal arrangements in the execution of extradition of perpetrators of corruption committed by the Police based on the Constitution of the ICPO-Interpol, and what factors hinder the Police in carrying out international cooperation in the field of extradition. The result of the discussion of the problems that arise in this research is an international cooperation agreement that has been ratified by the two countries, in which the Indonesian Police submitted a request for extradition as a requesting state to the requested state against the fleeing corruption perpetrator. The state government is requested to process the extradition request accompanied by authentic evidence of the complete identity of the perpetrator. The process of carrying out extradition was hampered due to several factors, one of which was the absence of an extradition agreement by the Government of Indonesia with the government of the requested country, where the perpetrators of corruption fled so that the implementation of extradition was hampered or perhaps even rejected by the requested country.